PS01.122: LONG-TERM QUALITY OF LIFE IN PATIENTS AFTER MCKEOWN VERSUS IVOR LEWIS ESOPHAGECTOMY. (14th September 2018) - Jezerskyte, Egle; Gisbertz, Suzanne; Van Berge Henegouwen, Mark I; Saadeh, Luca; Scarpa, Marco
Abstract: Background: Treatment of distal esophageal and gastroesophageal junction (GEJ) cancers is challenging. The therapy for these cancers mainly consist of (neo)adjuvant chemo(radio)therapy and surgery. There are different surgical approaches possible for these patients: transthoracic esophagectomy with a cervical anastomosis (McKeown) or an intrathoracic anastomosis (Ivor Lewis). However, there is no evidence which is the preferred approach in terms of oncology, morbidity and quality of life. The aim of this study was to investigate the difference in the long-term quality of life in patients undergoing McKeown (McK) versus Ivor Lewis (IL) esophagectomy in a tertiary referral center. Methods: Consecutive patients after either McK or IL for distal oesophagus, GEJ or proximal gastric carcinoma were asked to fill in EORTC QLQ-C30 and EORTC QLQ-OG25 questionnaires to evaluate quality of life during the period of January 2014 – December 2017. EORTC QLQ-INFO25 quality of life questionnaire was used to evaluate information needs of patients in both groups. All answers with a long follow up (> 1 year) after surgery were analysed. Results: In the McK group 62 and in the IL group 110 patients were included. Median follow up was 3 years for McK and 2 years for IL. Median age was 62, 4 years. Cognitive functioning was significantly better in the IL group ( P  = 0.038). Complaints of dyspnoe ( P  = 0.004) and dysphagia ( P  = 0.028) were significantly higher in the McK group. Patients after IL had significantly less trouble with eating with others ( P  = 0.003), trouble with taste ( P  = 0.032), chocking when swallowing ( P  = 0.022) and trouble with talking ( P  = 0.038). There was no significant difference in global health status or physical, role, social or emotional functioning. Furthermore there was no difference in symptoms of nausea, fatigue, pain, discomfort or information scores between McK and IL groups. Conclusion: After a follow up of > 1 year no differences in global health status or physical, role, social or emotional functioning scales between McK and IL esophagectomy were found. However, significant differences in some symptom scales and cognitive functioning were observed in favor of IL. These findings should be taken into consideration when deciding between a McK and IL esophagectomy in patients where both procedures are feasible. Disclosure: All authors have declared no conflicts of interest.